(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The aim of study was to estimate the level of pollution with some heavy metals including copper (Cu), cadmium (Cd), lead (Pb), iron (Fe) and chromium (Cr), dissolved and particulate matter in water and the exchangeable fraction in sediments, and considering them as an indicator for monitoring pollution with heavy metals in some areas of Wasit Province. Five sites were selected and approximately 10 km from one site to another. It extended from Al-Numaniyah District, through Al-Ahrar District, and ended in Al-Kut District, with a total distance of 50 km. The results showed that the concentrations of copper, cadmium, iron, lead, and chromium in the dissolved form of water have reached 0.49, 0.05, 2.97, 2.40, and 0.13 μg/L-1, respectively, while their rates in the particulate reached 27.42, 0.65, 1015.52, and 18.53. and 22.98 μg/g-1 dry weight, respectively, The exchange fraction of these metals in the sediment was 13.15, 0.58, 568.96, 31.43, and 30.67 μg/g-1 dry weight, respectively. The results also showed that the levels of heavy metals in their dissolved form were within the WHO limits, while in the particulate form the iron element was outside those limits. The rates of these metals in the sediments were high values in all study sites, with the values of the particulate form of these metals being superior to the dissolved form.